Albinarrate, Fernando. Entre las notas. Buenos Aires: Ediciones Ciudad de las Artes (Colección “Ensayos” - Universidad Nacional de las Artes), 2024, 232 p. ISBN: 978-631-90727-0-9 - Albini, María Claudia (2025)
Fil: Albini, María Claudia. Universidad Nacional de las Artes; Argentina